(untitled) (Journal of Economics and Management Research, 2023)
ملخص: هدفت هذه الدراسة الى شرح أهم المفاهيم المتعلقة بالتكنولوجيا المالية وضرورة رقمنة الجهاز المصرفي الجزائري لكي يستوعب التطورات الحاصلة في المنظومة المالية العالمية في ظل الثورة الرقمية، وانتشار ظاهرة الشمول المالي. ولقد توصلت الدراسة الى أن الجزائر تعاني من ظاهرة الاقتصاد غير الرسمي والتي تخفض من الإيرادات الضريبية للدولة، ولازالت الجزائر تبذل الكثير من الجهود من أجل رقمنة الجهاز المصرفي الجزائري وخلق بنية تحتية داعمة للتحول الرقمي ولكنها لازالت متأخرة، وذات معدل منخفض في الشمول المالي. Abstract This study aimed to explain the most important concepts related to financial technology and necessity of digitizing the Algerian banking system in order accommodate developments in the glogl financial system in light of the digital revolution, and the spreed of the phenomenon of financial inclusion. The study concluded that Algeria suffers from informal economy¸wich reduces the state’s tax revenues, and Algeria is still making a lot of effrts to digitize the Algerian banking system and create an infrastructure supportive of digital transformation.